CEO chairman controversy: evidence from the post financial crisis period - Gontarek, Walter; Belghitar, Yacine (Springer, 2020)
Regulators generally discourage bank CEOs also holding the role of board Chairman, as this governance structure can hinder independent decision-making and effective risk oversight. This study examines the issue of CEO Duality, identifying a positive relation to greater risk-taking across a battery of sensitivity tests. In further analysis, the study controls for differences in supervisory monitoring levels to examine its impact. Banks led by CEO Chairmen which are subject to lower levels of supervision continue to report a robust association to risk-taking, as before. However, this association dissipates for banks which are subject to heightened supervisory monitoring. These findings indicate that agency costs related to Duality may be moderated by greater regulation. This paper weighs-in on the controversy relating to a single contentious governance structure (i.e., CEO Duality), thus informing boards, regulators and researchers of the need to consider the overall interplay of monitoring mechanisms.
Keywords: Duality; Monitoring and risk governance; Agency-costs; BHCs; Risk-taking